Tropical peatlands under siege: The need for evidence-based policies and strategies - Murdiyarso, D.; Lilleskov, E.A.; Kolka, R. (Springer, 2019)
It is widely known that tropical peatlands, including peat swamp forests (PSFs), provide numerous ecosystem services in both spatial and temporal dimensions. These include their role as large stores for organic carbon, which when not managed well could be released as carbon dioxide and methane, accelerating climate warming. Massive destruction and conversion of peatlands occur at an alarming rate in some regions. We hope that the lessons learned from those regions currently under siege from conversion can inform other regions that are at the precipice of mass conversion to agriculture. Much has been learned about high latitude, northern hemisphere peatlands but less is known about tropical peatlands. We collate, analyze, and synthesize the evidence revealed from the set of articles in this special issue. This special issue is a step forward, presenting new information generated from a considerable amount of field data collected from peatlands across the tropics in Asia, Africa, and Latin America. The hard data collected using comparable scientific methodologies are analyzed and compared with existing published data to form a larger dataset as scientific evidence. The synthesis is then interpreted to generate new knowledge to inform the policy community on how to strategize the sustainable management of tropical peatlands. Carbon (C) stocks in tropical peatland ecosystems can be as large as 3000 Mg C ha−1, but the rate of loss is also phenomenal, causing substantial emissions of greenhouse gases of more than 20 Mg C ha−1 year−1. These losses have mainly taken place in Southeast Asia, particularly Indonesia, where peatland development for oil palm and pulpwood has accelerated over the past few decades. Although peatlands in the Amazon and Congo Basin are less developed, it is possible that the same unsustainable pathway would be followed in these regions, if lessons from the dire situation in Southeast Asia are not learned. Strong policies to halt further loss of tropical peatlands may be drawn up and combined with incentives that promote a global agenda under the United Nations Framework Convention on Climate Change 21st Conference of the Parties, Paris, France, Agreement. However, we also propose a framework to address national and local agendas that can be implemented under the nationally determined contributions (NDCs) by balancing conversion/development and conservation/restoration objectives.